Determining multiple intelligences pre-school children (4-6 age) in learning process - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
The study investigated the 4-to-6-year-old children's tendency of using intelligence types in learning regarding the Multiple Intelligence Theory and it focused on determining whether children's intelligence types differ according to their parents' educational level and socioeconomic status. A sample of 232 children and their parents participated in the study. The results related with the gender distribution ascertained that both girls and boys predominantly preferred visual-spatial intelligence as their first choice. It was also divulged that there was a statistically significant relationship between children's intelligence types and their parents' education level and their socioeconomic status. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Pre-school Education; Intelligence; The Theory of Multiple Intelligences and Learning